1973
DOI: 10.1042/cs045018pb
|View full text |Cite
|
Sign up to set email alerts
|

Control Mechanisms in Infectious Mononucleosis

Abstract: The blood mononuclear cells from forty-six patients with infectious mononucleosis were separated into populations of normal and atypical cells by velocity sedimentation. Both populations were characterized in terms of surface markers and response to standard mitogens. The atypical cells were of both T-and Blymphocyte origin. Some reactivity of the normal against the freshly isolated atypical cells was detected by mixed lymphocyte reactions and 51Cr release, but this was less marked than that obtained against a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1975
1975
1983
1983

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Earlier reports (4)(5)(6)(7) have demonstrated that a high proportion of the blast-transformed cells in the peripheral blood of IM patients are T-cell-derived. We and others have speculated that these T cells might be instrumental in bringing about the self-limitation of the disease (14,7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier reports (4)(5)(6)(7) have demonstrated that a high proportion of the blast-transformed cells in the peripheral blood of IM patients are T-cell-derived. We and others have speculated that these T cells might be instrumental in bringing about the self-limitation of the disease (14,7).…”
Section: Discussionmentioning
confidence: 99%
“…We and others have speculated that these T cells might be instrumental in bringing about the self-limitation of the disease (14,7). Since EBV is known to be the cause of IM our approach to this problem was to investigate whether IM blood contained effector cells with cytotoxic specificity for EBV-genome-carrying target cells.…”
Section: Discussionmentioning
confidence: 99%
“…Prim ary infection by EB virus is commonly associated with the self-limited lymphoproliferative disease infectious mononucleosis. T he m ajor p art of the characteristic atypical lymphocytosis consists of activated m ononuclear cells participating in the host response to B lymphocytes infected with EBV (Denm an & Pelton 1974;Svedmyr & Jondal 1975). This point was established by experiments in vitro in which the lymphocytes of patients with infectious mononucleosis were shown to be cytotoxic for lymphoblastoid cell lines transformed by EB virus.…”
Section: S Pecific Suppression Of a Ntiv Ira L Immunitymentioning
confidence: 99%
“…The self-limited disease infectious mononucleosis could represent a clinical expression of a controlled EBV-induced lymphoproliferative state. Recently, it has been reported that patients with tbis disease have circulating lymphocytes which are specifically cytotoxic to EBV-carrying cell lines (Denman & Pelton 1974. Unfortunately, no studies of cell-autogenous markers in EBV-carrying infectious mononucleosis cells have been reported.…”
Section: Malignant Lymphoid Proliferotionmentioning
confidence: 99%